A Novel Mental Health Crisis Service – Outcomes of Inpatient Data - Morrow, R (Ulster Med J, 2016)
INTRODUCTION: Northern Ireland has high mental health needs and a rising suicide rate. Our area has suffered a 32% reduction of inpatient beds consistent with the national drive towards community based treatment. Taking these factors into account, a new Mental Health Crisis Service was developed incorporating a high fidelity Crisis Response Home Treatment Team (CRHTT), Acute Day Care facility and two inpatient wards. The aim was to provide alternatives to inpatient admission. The new service would facilitate transition between inpatient and community care while decreasing bed occupancy and increasing treatment in the community. METHODS: All services and processes were reviewed to assess deficiencies in current care. There was extensive consultation with internal and external stakeholders and process mapping using the COBRAs framework as a basis for the service improvement model. The project team set the service criteria and reviewed progress. RESULTS: In the original service model, the average inpatient occupancy rate was 106.6%, admission rate was 48 patients per month and total length of stay was 23.4 days. After introducing the inpatient consultant hospital model, the average occupancy rate decreased to 90%, admissions to 43 per month and total length of stay to 22 days. The results further decreased to 83% occupancy, 32 admissions per month and total length of stay 12 days after CRHTT initiation. DISCUSSION: The Crisis Service is still being evaluated but currently the model has provided safe alternatives to inpatient care. Involvement with patients, carers and all multidisciplinary teams is maximised to improve the quality and safety of care. Innovative ideas including structured weekly timetable and regular interface meetings have improved communication and allowed additional time for patient care.